Meningkatkan Kualitas Pelayanan Kesehatan bagi Penyandang Disabilitas Netra melalui Inovasi Braille - Zhafirah, Farah; Enggra Saputri, Ellen; Ramadhan, Syahrul; Roziqin, Ali (Universitas Islam Malang, 2021)
Public service is something that can be accessed by the community, including for people with disabilities. Changes in the public needs of the community including people with disabilities are growing so that it requires an innovation that can equalize it. Public service innovation is a method for increasing change in order to encourage improvement in the quality of public services. Therefore, the City Government of Malang seeks to improve health services specifically for people with visual disabilities by forming innovations in the form of Braille. Braille innovations were made by the government in order to create equitable public services in the community. The government's goal to make this innovation is in order to create equitable public services in the community. In addition, this innovation is a form of commitment of Malang City to inclusive services and a form of commitment to alignments specifically for people with visual impairments. This study aims to determine the ability of Braille innovation in improving health services for people with visual impairments. The method used in this research is the study of literature. As in the application of innovation, there are driving and inhibiting factors. The driving factor is in the form of support from the Mayor of Malang through Malang City Regulation No. 2 of 2014 and officers receive training. Whereas the inhibiting factor of this innovation is only when building a guiding block that requires quite a lot of costs. However, the innovations provided are able to improve the quality of health services to the community. Even now, Puskesmas Janti Malang has become the first referral health service pilot site for people with visual impairments to receive treatment.